Effect of high energy electron exposure of the saline solution on physicochemical properties and cytotoxic activity of doxorubicin - M. A. Zabolotnyy; L. I. Aslamova; G. I. Dovbeshko; O. P. Gnatyuk; V. B. Neimash; V. Yu. Povarchuk; V. E. Orel; D. L. Kolesnyk; L. M. Kirkilevska; G. I. Solyanyk (Ядерна фізика та енергетика)
The effect of preliminary irradiation of an aqueous solution of sodium chloride (saline) with 1 MeV high-energy electron beams on optical and cytotoxic/cytostatic properties of the dissolved Doxorubicin cancer drug is studied. With the use of Lewis lung carcinoma cell culture, it has been shown that the said treatment results in an increased cytotoxic/cytostatic action of the Doxorubicin, being the most pronounced in the range of low concentrations of the drug. The delivered dose of ionizing radiation on the saline ranged from 4 to 80 kGy. The maximum changes in the IR absorption spectra of Doxorubicin have been observed for the solutions irradiated with 10 kGy. The possible causes of the observed effects are discussed.